EBV reduces autophagy, intracellular ROS and mitochondria to impair monocyte survival and differentiation. Issue 4 (3rd April 2019) - Gilardini Montani, M.S.; Santarelli, R.; Granato, M.; Gonnella, R.; Torrisi, M.R.; Faggioni, A.; Cirone, M.
ABSTRACT: EBV has been reported to impair monocyte in vitro differentiation into dendritic cells (DCs) and reduce cell survival. In this study, we added another layer of knowledge to this topic and showed that these effects correlated with macroautophagy/autophagy, ROS and mitochondrial biogenesis reduction. Of note, autophagy and ROS, although strongly interconnected, have been separately reported to be induced by CSF2/GM-CSF (colony stimulating factor 2) and required for CSF2-IL4-driven monocyte in vitro differentiation into DCs. We show that EBV infects monocytes and initiates a feedback loop in which, by inhibiting autophagy, reduces ROS and through ROS reduction negatively influences autophagy. Mechanistically, autophagy reduction correlated with the downregulation of RAB7 and ATG5 expression and STAT3 activation, leading to the accumulation of SQSTM1/p62. The latter activated the SQSTM1-KEAP1- NFE2L2 axis and upregulated the anti-oxidant response, reducing ROS and further inhibiting autophagy. ROS decrease correlated also with the reduction of mitochondria, the main source of intracellular ROS, achieved by the downregulation of NRF1 and TFAM, mitochondrial biogenesis transcription factors. Interestingly, mitochondria supply membranes and ATP required for autophagy execution, thus their reduction may further reduce autophagy in EBV-infected monocytes. In conclusion, this study shows for the first time that the interconnected reduction of autophagy, intracellular ROS and mitochondria mediated by EBV switches monocyte differentiation into apoptosis, giving new insights into the mechanisms through which this virus reduces immune surveillance. Abbreviations: ACTB: actin beta; ATG5: autophagy related 5; BAF: bafilomycin A1 ; BECN1: beclin 1; CAT: catalase; CSF2: colony stimulating factor 2; CT: control; CYCS (cytochrome C: somatic); DCs: dendritic cells; EBV: Epstein-Barr virus; GSR: glutathione-disulfide reductase; KEAP1: kelch like ECH associated protein 1; IL4: interleukin 4; MAP1LC3/LC3: microtubule associated protein 1 light chain 3; MET: metformin; NAC: N-acetylcysteine; NFE2L2/NRF2 nuclear factor: erythroid 2 like 2; NRF1 (nuclear respiratory factor 1); clPARP1: cleaved poly(ADP-ribose) polymerase; Rapa: Rapamycin; ROS: reactive oxygen species; SQSTM1/p62: sequestosome 1; TFAM: (transcription factor A: mitochondrial); TUBA1A: tubulin alpha 1a.